Hydrobiological Study of the Yamuna River at Kalpi, District Jalaun, Uttar Pradesh, India - Shukla, Manoj Kumar; Khare, Pushpendra Kumar; Singh, Ravindra (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
Hydro biological study of the Yamuna river at Kalpi in India was carried out for a period of twelve month (October 2013 to September 2014). Four sampling stations were selected for sampling purpose. Collected samples were evaluated for fourteen physico-chemical parameters such as W.T., pH, Conductivity, Turbidity, T.D.S., T.H., T.A., Cl, SO4, PO4, NO3, D.O., B.O.D. and C.O.D. and four biological parameters such as phytoplankton, zooplankton, aquatic macrophytes and fishes. Present study reveals that water quality of the Yamuna river was not fit for drinking purpose but it was satisfactory for fish culture and irrigation purpose. Presence of both pollution tolerant and pollution intolerant species of biological parameters shows that this water was moderately polluted during course of study. HYDRO Nepal Journal of Water Energy and Environment Volume- 18, 2016, January Page -41 to 46